A study of the production system of Prochem Consumer Products, Inc. - Dolor, Katherine (College of Engineering, 2002)
Prochem Consumer Products, Inc. is a manufacturing company that produces subcontracted soaps and company owned soaps. Since soap is a commodity, there is a need for the company to meet demands of clients and customers. The group was able to identify three main P/OM problems of the company. These are as follows: 1.Absence of formal forecasting technique; 2.High inventory holdings; and 3.Unbalanced Scheduling of machines. For each major problem, alternatives and recommendations were proposed and analyzed. The first problem which is the absence of forecasting technique, the group proposed that thy should implement the use of forecasting technique in order to lessen the error in demand anticipation. The use of the exponential smoothing method helps minimize errors and percent difference between actual demand and actual production. The second problem which is concerned with the high inventory holdings of the company, the group recommended the reduction of inventory level with the use of the continuous review system. The company should review if inventory is enough to meet demands before production begins. Also, with the aid of forecasting inventory holdings can be reduced. The last problem which is concerned with the unbalanced scheduling of the machine, particularly the Shen Seung 2 should be sold. Two machines can suffice the production level needed by the company. In addition, the group also proposed that the layout should be changed. That is, the storage of the additives should be placed near the mixing areas so as to minimize materials handling and load distance score.